Financial performance of sharia life insurance companies in Indonesia - Pratiwi, Permata Dian; Nofiyasari, Mela (Journal of Management and Business Insight, 2023)
Purpose-The objective of this study is to analyze the financial standing of Indonesian Sharia life insurance firms, which will be assessed in terms of profit and influenced by premium income, investment return, and risk-based capital. Sharia insurance aims to help each other by setting aside funds in accounts for the purpose of helping each other in case of an accident. Indonesia has a majority Muslim population, making Sharia insurance easy to develop. The development of Sharia insurance is expected to be in line with its financial performance. Design/Methodology/Approach-This research used a quantitative approach and secondary data. The sample used was Sharia life insurance companies registered with the Association of Sharia Insurance Indonesia during the period 2016-2021, with a total of 8 companies collected through purposive sampling. Hypothesis testing in this study used panel data regression analysis. Findings-The findings of this study demonstrated that premium income and risk-based capital had little bearing on the profitability of Indonesian Sharia life insurance firms. In the meanwhile, Indonesian Sharia life insurance companies' profits are impacted by investment return. The results of this study contribute to customers and companies to pay attention to financial performance and risk management. Research Limitations/Implications-This study has limitations due to a small sample size. It may prevent the findings from being extrapolated. Originality/Value-The investment capability of Sharia life insurance companies in Indonesia has shown good performance, which can generate profits. However, the signaling information from the premium decision-making capability and risk-based capital still does not meet the standard and needs to be improved.